Removal of hexavalent chromium by a microbial mat from a mining site under anaerobic conditions - Khan, Mohammad Tariq Ali; Al-Siyabi, Sumaiya Said; Ali, Hamada E.; Abed, Raeid M. M. (Frontiers in Bioengineering and Biotechnology, 2025)
Mining activities have contributed to increased contamination of groundwater with hexavalent chromium (Cr(VI)). Microbial mats have been shown to effectively remove Cr(VI) under aerobic conditions, however, their role in Cr(VI) removal under anaerobic conditions remained unexplored. This study investigates the removal of Cr(VI) by a microbial mat collected from a chromite mining site under anaerobic conditions, as well as the underlying mechanism(s). Removal rates of Cr(VI) increased from 0.15 ± 0.01 to 0.77 ± 0.05 mg L-1 d-1 when the mat was incubated at increasing concentrations from 5 to 50 mg L-1, respectively. Biosorption was facilitated by the increased production of extracellular polymeric substances (EPS) after exposure to Cr(VI) with the involvement of functional groups such as metal-O, Cr(VI)-O, PO4, C-N, C=O, C-H, Alkyl, and OH-NH2. The mat could also reduce Cr(VI) to Cr(III) using chromate reductase enzyme. MiSeq sequencing demonstrated clear shifts in the bacterial community structure in favor of Clostridia and Bacilli at 1 mg L-1 Cr(VI), Gammaproteobacteria at 5 mg L-1 Cr(VI), and Alphaproteobacteria at the concentrations of 15–50 mg L-1 Cr(VI). We conclude that microbial mats contain obligate and facultative anaerobic bacteria that possess the ability to remove Cr(VI) under low fluctuating oxygen levels by biosorption on cell surface and enzymatic reduction to Cr(III).